2019
DOI: 10.1111/liv.14126
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of direct‐acting antivirals for hepatitis C in the elderly: A systematic review and meta‐analysis

Abstract: Background&Aims Since the introduction of direct‐acting antivirals (DAAs) several studies have reported high efficacy and safety in Hepatitis C infected patients, even in those earlier considered difficult‐to‐treat. We aimed to assess the efficacy and safety of DAA therapy in elderly patients. Methods The PubMed MEDLINE, Embase and Cochrane databases were searched through July 2018. Two independent researchers extracted data and assessed the quality and risk of bias. Risk ratios (RRs) were pooled using random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…In previous studies, the age of 65 yo has been the most often selected as a threshold while 75 yo is a rarer choice [4] . In the meta-analysis of Mücke et al [5] , the DAA treatment was similarly effective in patients aged >65 yo when compared with the younger population. Subgroup analysis also revealed a comparable risk for non-SVR when evaluating studies assessing patients who were <75 yo vs >75 yo.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In previous studies, the age of 65 yo has been the most often selected as a threshold while 75 yo is a rarer choice [4] . In the meta-analysis of Mücke et al [5] , the DAA treatment was similarly effective in patients aged >65 yo when compared with the younger population. Subgroup analysis also revealed a comparable risk for non-SVR when evaluating studies assessing patients who were <75 yo vs >75 yo.…”
Section: Discussionmentioning
confidence: 92%
“…Before these drugs became available, the treatment was based on interferon, which had limited benefits for elderly patients due to its low safety profile and poor efficacy [3] . Many studies have reported the results of DAA treatment in elderly patients, the most recent in 2019 [4] , with a meta-analysis carried out in 2019 [5] . The studies were primarily focused on SVR 12 rates and incidence of undesirable effects, fixing the maximum age of inclusion at 65 or 75 years old (yo).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, SVR achieved with all‐oral DAAs is durable, and importantly, as durable as that obtained through IFN‐based therapy. Furthermore, due to the low risk of HCV recurrence even in the high‐risk HCV mono‐infection and HIV/HCV co‐infection populations, there would appear to be no reason to withhold or defer DAAs therapy in patients who remain at risk for reinfection 66‐70 …”
Section: Discussionmentioning
confidence: 99%
“…Two meta-analyses reviewed clinical trials and post-marketing studies to evaluate the efficacy and safety of DAA regimens in the elderly population [34,35]. Overall, DAA therapies are highly effective and well-tolerated in patients ≥ 65 years old.…”
Section: Real-world Experiencementioning
confidence: 99%